Phytoplankton dynamics and their role in carbon sequestration across different oceanic zones - Sultanov, Ogabek; Bobojonov, Safarali; Almusawi, Muntadher Muhssan; V, Ayyappan; Bobojonova, Dilorom; Nayak, Ashu (International Journal of Aquatic Research and Environmental Studies, 2025)
Phytoplankton are key elements in the oceanic carbon cycle. They contribute to roughly fifty percent of global primary productivity and enable carbon storage through the biological pump. This study examines phytoplankton carbon sequestration across spatially discrete oceanic zones, including coastal shelves, oligotrophic open oceans, and upwelling systems. To evaluate spatial-temporal variability during 2010–2020, satellite-derived chlorophyll-a concentrations (MODIS-AQUA), additional datasets, and in-situ observations were integrated with a coupled physical-biogeochemical model. The analysis results display substantial variance in phytoplankton biomass and productivity due to changes in nutrient fluxes, light availability, sea surface temperature (SST), and mixed layer depth. Upwelling regions exhibited higher primary production and carbon export efficiencies than the rest of the ocean, with increased particulate organic carbon (POC) fluxes resulting from diatom-dominated communities. In contrast, oligotrophic gyres were characterized by low-biomass picophytoplankton communities, which reduced vertical carbon export. These results demonstrate marked differences in the contributions of oceanic provinces to carbon sequestration, indicating that changing climate conditions could significantly affect biogeochemical processes. The research enhances understanding of the oceanic carbon sink and highlights the need for spatially explicit carbon cycle models for climate mitigation.
Keywords: Phytoplankton; Carbon; Ocean; Picophytoplankton; Biomass; Climate mitigation